THE RIGHT TO A HEALTHY ENVIRONMENT IN INTERNATIONAL HUMAN RIGHTS LAW - Seher Çakan (Ankara Sosyal Bilimler Üniversitesi Hukuk Fakültesi Dergisi)
The exercise of human rights is adversely affected by environmental degradation. Nevertheless, linking human rights to the right to a healthy environment is just one aspect of this right. The other aspect is environmental degradation, which currently does not negatively affect human rights. However, these environmental degradations may adversely affect human rights in the long term. This broader right covers ecological and ecosystem degradation, development, and protection in this context. A safe, clean, healthy, and sustainable environment was recognized as a fundamental human right for the first time ever on a global scale with the adoption of the UN General Assembly's resolution. There are only a few conventions that directly contain this right. However, it does not follow that other accords do not also safeguard this righ.This study aims to define the concept and ascertain to what extent the right to a healthy environment is protected by international law.